Determination of Nicotine-Related Impurities in Nicotine Pouches and Tobacco-Containing Products by Liquid Chromatography–Tandem Mass Spectrometry - Rozanna Avagyan; Maya Spasova; Johan Lindholm (Separations, 2021)
Smokeless tobacco products and nicotine-containing tobacco-free oral pouches have increased in popularity in recent years. They are associated with far fewer health hazards compared to cigarettes. Nicotine pouches are filled with non-tobacco filler and nicotine. The nicotine used in nicotine pouches usually comes from the extraction of tobacco; thus, related alkaloids may be found as impurities at low levels. Moreover, nicotine degradation products are formed because of microbial action, flavor oxidation, exposure to high temperatures etc. Currently, there are no published or recommended methods for the analysis of nicotine degradants in nicotine pouches. Here, we present a sensitive and selective liquid chromatography–tandem mass spectrometry method for the simultaneous determination of seven nicotine-related impurities. All seven analytes and corresponding deuterated internal standards were separated within 3.5 min, including 1 min equilibration. The method was fully validated, showing good linearity with correlation coefficients >0.996 for all analytes, good extraction yields ranging from 78% to 110%, limits of detection between 0.08 and 0.56 µg/g and limits of quantification between 0.27 and 2.04 µg/g. Although the method was mainly developed to determine the degradants of nicotine in nicotine pouches, it was validated and performed well on a broader range of tobacco-containing products.